Mortgages, Risk, and Homeownership among Low- and Moderate-Income Families - Bostic, Raphael W; Lee, Kwan Ok (American Economic Review, 2008)
The utility of homeownership as a household wealth-building vehicle has long been recognized. In recent years, homeownership has been promoted as an important strategy for improving the financial situation of lowand moderateincome households. However, this strategy does not come without its risks, as homeownership exposes households to potential troubles along multiple dimensions. This paper highlights the conditions under which a homeownership strategy is likely to be effective. A key contribution is its significant focus on the risks of homeownership, which are assessed by studying the distribution of foreclosure across neighborhoods. According to the Current Population Survey (CPS), between 1994 and 2006, homeownership rates among households in the first and second income quartiles increased by 11.1 and 12.9 percent, respectively. This exceeded the 10.3 percent increase observed for the general population and was due in part to several factors. First, income, education, and wealth for lowand moderate-income households all increased significantly over this period (Arthur B. Kennickell 2006), which increased the accesAssets And Credit Among Low-inCome HouseHoLds †